Correlation between neutrophil/lymphocyte ratio and cognitive impairment in cerebral small vessel disease patients: A retrospective study - Hou, Lan; Zhang, Shuhan; Qi, Dandan; Jia, Tongle; Wang, Huan; Zhang, Wei; Wei, Shuyan; Xue, Conglong; Wang, Pei (Frontiers in Neurology, 2022)
Background and Objective: The blood neutrophil/lymphocyte ratio (NLR) is an objective and convenient parameter of systemic inflammation. Elevated NLR is associated with increased risk of mild cognitive impairment (CI) in the elderly. However, few data are available on the impact of the NLR on CI in patients with cerebral small vessel disease (CSVD). Methods: 66 CSVD subjects with CI and 81 without CI were evaluated in this study. Clinical, laboratory, radiological and cognitive parameters were collected. The NLR was obtained with the absolute neutrophil count being divided by the absolute lymphocyte count in fasting blood samples. Logistic regression analysis was performed to evaluate the factors associated with CI. Receiver operating characteristic curves were illustrated to predict the risk factors of CI in patients with CSVD. Results: The NLR of CI group was significantly higher than that of subjects without CI (2.59 vs. 2.21, P = 0.003). In multivariate analysis, NLR was an independent risk factor for CI (OR: 1.43, 95% CI: 1.05-1.96, P = 0.024). It was suggested that the optimum NLR cut-off point for CI was 1.89 with 69.7% sensitivity and 59.3% specificity. Subjects with NLR ≥ 1.89 showed higher risk relative to NLR < 1.89 (OR: 3.38, 95% CI: 1.62-7.07). Conclusions: Correlations were found between NLR and CI. CSVD patients with higher NLR might have increased risk of CI.